2006 International Conference of the IEEE Engineering in Medicine and Biology Society 2006
DOI: 10.1109/iembs.2006.260522
|View full text |Cite
|
Sign up to set email alerts
|

Action Potential Duration Gradient Protects the Right Atrium from Fibrillating

Abstract: Atrial fibrillation (AF) is the most common cardiac arrhythmia. It is characterized by rapid and disorganized electrical activity in the atria. Atrial arrhythmias can be triggered from an ectopic focus, i.e., an abnormal impulse originating in an area other than the sinus node, generating reentrant waves. The regional ionic heterogeneities found in the atria cause a gradual shortening of the action potential duration (APD) with increased distance from the sinoatrial node. It is generally thought that the only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Models of the atria have been based on the histologically reconstructed Visible Female human geometry (Harrild & Henriquez, 2000; Seemann et al, 2006; Cherry & Evans, 2008). Reconstructions based on volumetric MRI (Jacquemet et al, 2006) and CT (Ridler et al, 2006) have also been used to obtain generic surface geometries of the atria. While these models included various details of atrial anatomy, their segmentation into electrophysiologically and anatomically distinctive tissue sub-domains was either absent (Harrild & Henriquez, 2000; Jacquemet et al, 2006; Cherry & Evans, 2008) or based on phenomenological estimations of the sub-domain locations (Ridler et al, 2006; Seemann et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Models of the atria have been based on the histologically reconstructed Visible Female human geometry (Harrild & Henriquez, 2000; Seemann et al, 2006; Cherry & Evans, 2008). Reconstructions based on volumetric MRI (Jacquemet et al, 2006) and CT (Ridler et al, 2006) have also been used to obtain generic surface geometries of the atria. While these models included various details of atrial anatomy, their segmentation into electrophysiologically and anatomically distinctive tissue sub-domains was either absent (Harrild & Henriquez, 2000; Jacquemet et al, 2006; Cherry & Evans, 2008) or based on phenomenological estimations of the sub-domain locations (Ridler et al, 2006; Seemann et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Biophysically detailed three-dimensional computational models have been developed for major parts of the heart [7,9], with several models accounting for various details of atrial electrophysiology and anatomy [8,9,[26][27][28][29]. Comprehensive review of such models can be found elsewhere [9].…”
Section: Comparison With Other Modelsmentioning
confidence: 99%
“…Computational modelling provides a quantitative framework for integrating such multi-scale data and understanding the arrhythmogenic behaviour that emerges from the complex and collective spatio-temporal dynamics in all parts of the heart, across all scales and in various conditions (Rudy, 2000; Noble, 2005; Clayton et al, 2011). However, due to the lack of complete experimental datasets from human (as well as for the reasons of computational efficiency), existing models of the atria use either simplistic descriptions of the electrical properties or idealized tissue structure and anisotropy (Harrild and Henriquez, 2000; Seemann et al, 2006; Jacquemet et al, 2006; Ridler et al, 2006). Therefore, there is a need for efficient and quantitative atrial models that integrate data at all of ionic channel, cellular, anisotropic tissue and whole atria levels, which are validated against clinical data from humans.…”
Section: Introductionmentioning
confidence: 99%